An analysis on the suitabililty of selected newspaper material as a teaching resource in efl courses. - Buitron, Mercy (2010)
The main purposes of this research are to show teachers how useful newspapers can be as an educational tool in their classroom, and to motivate students to improve the reading skills using the newspaper material. During the present study we have found that the process of acquiring a new language involves a great number of linguistic and cultural aspects considered in this research work. First of all, within the linguistic aspect, we had observed that the authors of the different articles, news and reports use standard language to seize every audience since newspapers are a means of communication to informed people of a particular event.